Case Study of Nursing Care For An Elderly Family With Hypertension Problems - Aneng Yuningsih (LPPM STIKes Muhammadiyah Ciamis, 2022)
Introduction: Hypertension is one of the health issues brought on by degenerative processes that many elderly people experience. The estimated number of hypertension cases in Indonesia is 63,309,620 people, with (55.2%) hypertension occurring in the 55-64 year age group, then (45.3%) in the 45-54 year age group, and (31.6%) in the age group 31-44 years. To reduce these cases, family nursing care is one strategy used, with a focus on five family health tasks: identifying health issues, making decisions about health issues for sick families, caring for sick families, changing the environment inside and outside the home that affects family health, and using health service facilities. Objective: To describe family nursing care at the growth and development stages of elderly people with hypertension problems. Method: Using descriptive methods with a case study approach. Results: Based on a case study conducted on five elderly families with hypertension, Diagnosis: Risk of Ineffective Cerebral Perfusion Disorders, Knowledge Deficit About Hypertension Control, Non-Compliance, Ineffective Family Health Management, and Ineffective Health Management Conclusion: The nursing care provided to the family resulted in the family nursing problems that emerged being partially resolved.